ARTBOTS IN SPECIAL EDUCATION: POSSIBLE APPLICATIONS AND BENEFITS (Proceedings of the International Conference on Education, 2022)
Artbots are moving toys and objects which draw automatically with simple materials and technologies combining art with science and technology in a way that equitably connects the components of the STEAM (Science, Technology, Engineering, Arts and Mathematics) approach's equation (STEM + Arts = STEAM) and dynamically opens further up to many other disciplines. This paper deals with possible applications of artbots activities in Special Education. It draws on relevant literature review about STEAM in education and Special Education and presents artbots’ concept. Furthermore, the methodology involves practice-based research through experiential workshops and implementation of artbots activities with children with disabilities. The views of Special Education teachers and professionals with regards to the benefits of artbots activities for children with different disabilities are also described. As population of children with disabilities constitute a highly heterogeneous group, emphasis will be placed upon specific examples of applications with children with different type of disabilities. It is argued that artbots activities should foster creativity, engagement, social interaction, motor and other skills and enrich learning process both in special and in inclusive educational settings.
Keywords: artbots; special education; STEAM; creativity; skills development